Pengembangan Media Pembelajaran Monopoly Games Smart Pada Materi Sistem Pencernaan di SMP - Ahmad Syofian; Syafii Nur Ahmmad Fauzi (Milenial: Journal for Teachers and Learning, 2021)
This study aims to develop, feasibility and compare differences in learning outcomes before and after using Monopoly learning media Smart Games on the topic of the digestive system at SMP IBA Palembang. Research applying the Research and Development method with steps, namely definition, design, and development. Egibility is based on the evaluation of media experts and small-scale trials. Collecting data in this study using interviews, questionnaire and documentation. The analysis technique includes product data analysis. Research result shows that the learning media Monopoly Games Smart (MGS) is influential significant in improving concept mastery. Based on concept mastery students show that the application of learning uses Monopoly Games Smart is better than conventional. Learning process on system material digestion is felt to be more effective and student-centered which makes students more active in learning and make the learning process more meaningful. If the response good learning, then understanding the concept of the material will also be good.